Rekayasa Penilaian di Online Shop : Studi Perbandingan Hukum Ekonomi Syariah dan Hukum Positif Indonesia - Ahnan, Maftuh; Maghfur, Maghfur; Lestari, Dian (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
The purpose of this research is to analyze the engineering of reviews conducted by online stores on the Shopee platform, as well as to review their validity and implications based on the Sharia Economic Law and the Indonesian Positive Law. The research conducted uses a qualitative type. In accordance with the issues raised, using field research. The data sources in this study, namely primary data sources, were obtained through interviews with business actors who use the shopee marketplace platform. Secondary data sources are obtained from books and research reports related to the Salam sale and purchase agreement. Based on the analysis of Islamic economic law, it is not appropriate because the shop does a fake review first to attract customers, this method is not in accordance with Islamic law because it contains elements of gharar, shop owners should be able to use promotional methods for their business in accordance with buying and selling in general. Meanwhile, from the perspective of Indonesian positive law, fictitious orders are a form of criminal fraud that harms others and is regulated in the ITE law with a penalty of up to 12 years in prison or a fine of Rp12 billion. This research makes a scholarly contribution by examining the practice of valuation engineering in the market from the perspective of Shariah economic law, thus enriching the literature on business ethics and consumer protection in Shariah-based online buying and selling transactions.